KELAYAKAN MENIKAH PADA PEREMPUAN DAYAK DI LERENG PEGUNUNGAN MERATUS - Yusna Zaidah; Fajariah; Fauziah Hayati (CV. Lafadz Jaya, 2026)
Abstract The normative eligibility for marriage for women is set at a minimum age of 19 years, but its implementation faces challenges in customary law communities that have their own standards of readiness. Marriage for the Dayak people on the slopes of the Meratus Mountains is a complex process involving cultural, economic and psychosocial dimensions. Amidst the tide of modernisation, the criteria for marriage eligibility for Dayak women deserve attention. This qualitative research using an ethnographic approach aims to explore the criteria for marriage readiness for Dayak Meratus women and identify the factors that influence the establishment of these criteria. Data was collected through participatory observation and in-depth interviews with Dayak women, traditional leaders, and family members to understand the gap between formal regulations and local wisdom standards, as well as the factors behind it. The findings show that marriage eligibility for Dayak Meratus women focuses more on physical readiness (ganal awak) and mental readiness (kawa diharap) than age. This is influenced by factors such as the agrarian economic structure that places women as productive units, access to education in mountainous areas, and the social function of marriage as a strategy for strengthening kinship and protecting land. This has a significant impact on the high rate of early marriage in the region.